Ragam Bahasa Gaul Pada Media Sosial: Analisis Sosiolinguistik Terhadap Identitas Generasi Z - Linarsih, Yanti; Kusyairi, Kusyairi; Khoiri, Khoiri (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
Social media has become the main arena of communication for Generation Z, who are widely recognised as digital natives. A prominent linguistic phenomenon in their interaction is the use of slang, which is creative, dynamic, and rich in social meaning. This study aims to describe the forms of slang used on social media, analyse its social functions, and reveal its relation to the identity of Generation Z. The research employed a descriptive qualitative method with a sociolinguistic approach. Data were collected from posts, comments, and interactions of Generation Z on TikTok, Instagram, and Twitter/X through documentation, online observation, and note-taking. The analysis was carried out through identification, classification, and interpretation of social meaning. The findings indicate that slang encompasses new vocabulary, abbreviations, acronyms, code-mixing, and digital non-verbal symbols. Its social functions include strengthening solidarity, creating humour, delivering criticism, and asserting group identity. This study concludes that slang represents the identity of Generation Z and constitutes part of the dynamic development of the Indonesian language in the digital era.